Numerical investigation of non-linear inverse Compton scattering in double-layer targets - Galbiati, Marta; Formenti, Arianna; Grech, Mickael; Passoni, Matteo (Frontiers in Physics, 2023)
Non-linear inverse Compton scattering (NICS) occurring during the interaction of ultra-intense laser pulses with double-layer targets (DLTs) is studied with two-dimensional particle-in-cell simulations. The properties of this synchrotron-like photon emission are shown to be governed by the processes characterizing laser interaction with the near-critical and solid layers composing the DLT. In particular, electron acceleration, laser focusing in the low-density layer, and pulse reflection on the solid layer determine the radiated power, the emitted spectrum, and the angular properties of emitted photons. Analytical estimates, supported by simulations, show that quantum effects are relevant at laser intensities as small as 10^21 W/cm^2. Target and laser parameters affect the NICS competition with bremsstrahlung and the conversion efficiency and average energy of emitted photons. Therefore, DLT properties could be exploited to tune and enhance photon emission in experiments and future applications.